Combining Multispectral Imaging and XRF Analysis to Examine San Patroba predica ai fedeli di Pozzuoli by Massimo Stanzione - Jessica Brocchieri; Elvira Scialla; Marianna Merolle; Palma Maria Recchia; Roberto della Rocca; Carlo Sabbarese (Quantum Beam Science, 2023)
A diagnostic analysis of the painting depicting San Patroba che predica ai fedeli di Pozzuoli by Massimo Stanzione was carried out. The painting was completed in 1635–1637 to decorate the choir of the Cathedral of Saint Procolo in Pozzuoli (Naples, Italy). The technique of X-ray fluorescence (XRF) and multispectral imaging were applied on site to learn about the executive technique, the palette of the painting, and the restoration works, as well as understand the influence of the other painters active in Naples in that period. The results of the research are presented and discussed to draw general aspects and peculiarities of the pigments and the pictorial technique used by this important painter, as well as the restorations.